Optimalisasi Pembelajaran Akidah Akhlak Kelas IV melalui Pendekatan Inquiry- Discovery di Islamiyah Butoh - Imam Syafi’i; Alfi Elma Diana (Edumaspul: Jurnal Pendidikan, 2021)
AbstractEducation is currently still one of the most interesting topics to discuss, an education can be considered successful if it can produce generations that are ready to jump in and develop in society. This can be obtained by providing appropriate learning to students, one of which is by using the inquiry-discovery approach. Learning is very important to accelerate the understanding and skills of students, in this case an appropriate learning model is needed. In line with that, the discovery-inquiry learning model is a suitable model to be applied in learning at Madrasah Ibtidaiyah with the aim of implementing a more optimal learning. For the sake of creating Islamic character and full of courtesy, it is necessary to instill in children who can start early, namely by providing an understanding of morals through the Akidah Akhlah subject. The Akhlas subject itself can be obtained in Islamic schools, one of which is Madrasah Ibtidaiyah.Keywords : Optimization of Learning, Inquiry-Discovery Approach